2010
DOI: 10.1007/s11420-009-9129-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor: An Essential Component of Angiogenesis and Fracture Healing

Abstract: Fractures require adequate stability and blood supply to heal. The vascular supply to long bones is compromised in a fracture, and the ability to heal hinges on the ability of new blood vessels to proliferate from surrounding vessels in a process known as angiogenesis. This process is largely driven by the growth factor, vascular endothelial growth factor (VEGF), whose levels are increased locally and systemically during fracture healing. VEGF is involved in many steps throughout the fracture healing cascade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 70 publications
4
119
0
1
Order By: Relevance
“…Angiogenesis is important for providing oxygen, vital nutrients and cells essential for successful bone development, growth as well as fracture repair (Carano & Filvaroff 2003, Keramaris et al 2008, Tang et al 2012. Although fibroblast growth factor 2, platelet-derived growth factor (PDGFBB) and vascular endothelial growth factor (VEGF) have all been associated as angiogenic growth factors, VEGF has been identified as the key mediator for angiogenesis (Ogden 2000a,b,c, Keramaris et al 2008, Beamer et al 2010. In addition to VEGF's roles in the migration and proliferation of endothelial cells and blood vessel formation (Carlevaro et al 2000), VEGF receptors have also been localised on osteoblasts (Midy & Plouet 1994, Deckers et al 2000 and osteoclasts (Nakagawa et al 2000, Street et al 2002 -indicating the potential importance of VEGF in both angiogenesis as well as osteogenesis and bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is important for providing oxygen, vital nutrients and cells essential for successful bone development, growth as well as fracture repair (Carano & Filvaroff 2003, Keramaris et al 2008, Tang et al 2012. Although fibroblast growth factor 2, platelet-derived growth factor (PDGFBB) and vascular endothelial growth factor (VEGF) have all been associated as angiogenic growth factors, VEGF has been identified as the key mediator for angiogenesis (Ogden 2000a,b,c, Keramaris et al 2008, Beamer et al 2010. In addition to VEGF's roles in the migration and proliferation of endothelial cells and blood vessel formation (Carlevaro et al 2000), VEGF receptors have also been localised on osteoblasts (Midy & Plouet 1994, Deckers et al 2000 and osteoclasts (Nakagawa et al 2000, Street et al 2002 -indicating the potential importance of VEGF in both angiogenesis as well as osteogenesis and bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatments of these diseases, the role of angiogenesis has been demonstrated in numerous scientific reports (3)(4)(5). For example, physiological angiogenesis always occurs in the endometrium during the menstrual cycle, and appears in the basalis layer during menstruation and in the functionalis and subepithelial capillary plexus during the proliferative and early secretory stages (3).…”
Section: Discussionmentioning
confidence: 99%
“…Normal physiological angiogenesis is rarely observed in adults except in the ovary and endometrium during females' reproductive life (3). In numerous pathological conditions, angiogenesis is also required to facilitate tissue repair by transferring more nutrients and oxygen to the ischemia sites, which is beneficial to treat several types of illnesses, including myocardial ischemia, osteonecrosis, bone fracture and ischemic chronic wounds such as a diabetic limb (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LIPUS exposure group had higher new capirally vessel formation ratio in all layer of bone defected area at 7 days than control group (p < 0.05, data not shown). VEGF known as a key growth factor directly associated with angiogenesis and neovascularization is produced by endothelial cells, macrophages, fibroblast, smooth muscle cells and osteoblasts 22) . Some studies reported VEGF expression was upregulated by LIUPS exposure.…”
Section: Discussionmentioning
confidence: 99%